2008
DOI: 10.1007/s11010-008-9777-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of different isoforms of 14-3-3 protein family in human dermal and epidermal layers

Abstract: We have previously demonstrated a high level of stratifin, also known as 14-3-3 sigma in differentiated keratinocyte cell lysate and conditioned medium (CM). In this study, we asked the question of whether other 14-3-3 isoforms are expressed in human dermal fibroblasts, keratinocytes, intact dermal and epidermal layers of skin. In order to address this question, total proteins extracted from cultured cells or skin layers were subjected to western blot analysis using seven different primary antibodies specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Indeed, keratinocytes are known to release stratifin, also called MMP-14, which can stimulate the expression of MMP-1 and matrix breakdown by fibroblasts (Kilani et al, 2008(Kilani et al, , 2013Lam et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, keratinocytes are known to release stratifin, also called MMP-14, which can stimulate the expression of MMP-1 and matrix breakdown by fibroblasts (Kilani et al, 2008(Kilani et al, , 2013Lam et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…They are a ubiquitous family of acidic eukaryotic proteins [32]. Kilani et al [33] suggested that all 14-3-3 proteins are expressed by cells of the epidermal but not the dermal layer, and these proteins are mainly expressed by differentiated keratinocytes. The Western blot results showed that the level of total 14-3-3 expression was higher in skin treated with the laser relative to that without treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of 14-3-3 binding motifs have been established [5], and these have recently been reviewed [6]. Seven mammalian 14-3-3 isoforms have been reported (α/β, ε, γ, σ, ζ/δ, τ/θ and η) that are encoded by seven different genes and vary in their expression levels between tissues [7,8,9]. Moreover, highly redundant functions exist between the different 14-3-3 isoforms.…”
Section: Introductionmentioning
confidence: 99%